2015
DOI: 10.1371/journal.pone.0119822
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Meta-Analysis of Tuberculosis Contact Investigation Interventions in Eleven High Burden Countries

Abstract: BackgroundScreening of household contacts of tuberculosis (TB) patients is a recommended strategy to improve early case detection. While it has been widely implemented in low prevalence countries, the most optimal protocols for contact investigation in high prevalence, low resource settings is yet to be determined. This study evaluated contact investigation interventions in eleven lower and middle income countries and reviewed the association between context or program-related factors and the yield of cases am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
75
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 24 publications
8
75
1
1
Order By: Relevance
“…[19] Our findings are also consistent with previous work demonstrating that even members of vulnerable populations in Uganda have access to mobile phones. [20][21][22] Only 5% of index patients and 1% of contacts reported that they did not have access to a mobile phone, a functional precondition of household contact investigation in lowincome, urban settings where street addresses are uncommon.…”
Section: Forsupporting
confidence: 92%
“…[19] Our findings are also consistent with previous work demonstrating that even members of vulnerable populations in Uganda have access to mobile phones. [20][21][22] Only 5% of index patients and 1% of contacts reported that they did not have access to a mobile phone, a functional precondition of household contact investigation in lowincome, urban settings where street addresses are uncommon.…”
Section: Forsupporting
confidence: 92%
“…If neither is the case, then generalized risk estimates can be used. 3,9 Child contacts requiring evaluation The average number of children per household is estimated by dividing the number of children by the number of households. Multiplying the number of annually reported adult pulmonary TB cases by the average number of children per household estimates the number of child household contacts requiring evaluation in one year.…”
Section: Methods 1: Setting Programmatic Targets Using Locally Availabmentioning
confidence: 99%
“…Meta-analysis of these recent initiatives demonstrated that program yield and contribution to case detection are dependent on program design and implementation [9]. Eligibility criteria used to guide evaluation of contacts demonstrated that compared to the most restrictive criteria (≥ 2 weeks of cough) the adjusted odds ratio for lesser (any TB related symptom) and the least (all contacts) restrictive testing criteria were 1.71 (95% CI 0.94–3.13) and 6.90 (95% CI 3.42–13.93), respectively [9]. Furthermore, contact investigation contributed to between <1% to 14% of all sputum smear positive cases in the intervention areas.…”
Section: Introductionmentioning
confidence: 99%